Potential Health Benefits of Passion Fruit Peel Flour - E. Smith, Robert; M. da Silva Menezes, Ellen; U. O. Sabaa-Srur, Armando; Wycoff, Wei (Natural Products Journal, The, 2012)
Flour prepared from the peels of passion fruit (Passiflora edulis fo. flavicarpa O. Deg.) has been shown to have several health benefits. It has been shown to increase the concentration of high density lipoproteins (HDL) in blood, reduce the concentrations of glucose, cholesterol and LDL, as well as lower blood pressures and body weights in diabetic rats and people. Passion fruit peels are fed to cattle and there have been reports on their increasing milk production and preventing bacterial infections. The peel flour is mostly made of pectin, a dietary fiber. CP-MAS 13C-NMR was used to verify the composition of one sample, which produced chemical shifts (peaks) at 21 and 54 ppm. They were due to OCOCH3 and COOCH3, which are acetyl and methyl ester derivatives of polygalacturonic acid. There were also peaks due to glucuronic acid carbons 1-5 from 65–88 ppm, carbon-1 at 104 ppm and C-6 (carbonyls, acid and ester) at 172 ppm. This may prove to be a good method for verifying the identity of passion fruit peel flour.
Keywords: CP-MAS NMR